Implementation of Business Intelligence for Product Optimization to Enhance Profitability Through the Utilization of Synergies Among the Product Departments of the Look Company for the Period 2019-2022 - Oktori Kiswati Zaini; Kurniawan, Muhamad Segafi; Doni Wihartika (Journal of Social Transformation and Regional Development, 2024)
This research discusses the implementation of Business Intelligence (BI) to enhance the profitability of The Look Company through the synergy of product departments. In the era of big data, a company’s ability to process and analyse data becomes a crucial factor in achieving competitive advantage. This research aims to present data information from The Look Company’s Product Departments in the form of visualizations, graphs, and diagrams that can be used as indicators for decision-making. It also aims to identify products that are not generating significant profitability for the company in order to optimize production costs and to identify products that experience frequent cancellations and returns. This analysis and recommendations are intended to assist The Look Company in its decision-making process through the implementation of a comprehensive and detailed Business Intelligence study. Additionally, this research outlines the steps of data collection and processing methods using tools such as Google Colab, Postgree, and Tableau to generate visualizations, graphs, and diagrams that provide indicators and recommendations for decision-making within The Look Company. The research results indicate that the BI data visualization dashboard plays a crucial role in determining business strategies and providing rapid and accurate decision-making recommendations.